2020
DOI: 10.1590/0037-8682-0515-2020
|View full text |Cite
|
Sign up to set email alerts
|

Leprosy in children under 15 years of age in a municipality in northeastern Brazil: evolutionary aspects from 2003 to 2015

Abstract: Introduction: The Integrated Program of Leprosy Control was initiated in 2003 in the municipality of Buriticupu, Maranhão, Brazil, an area considered hyperendemic for leprosy. Here, we present the evolution of the indicators of leprosy within the established period in children aged <15 years. Methods: This is a descriptive study based on an active search for cases and spontaneous healthcare demand for leprosy, with an evolutionary analysis of the detection coefficient of new cases. We considered individuals ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…The present study showed that, despite Rio Grande do Sul State being historically a low endemic region, diagnoses of new cases in individuals under 15 years old that are multibacillary and present with a high average of physical disability continues to occur. These data are also found in studies in other regions of Brazil, showing that it is necessary to maintain active care and disease control measures, such as: promote training/updates on leprosy to health workers, so that they will think about the diagnosis of leprosy, especially in the early stages of the disease, and continue the annual monitoring of leprosy cases in all Brazilian States 16 , 19 , 20 , 33 . Especially in the studied age group, physical disabilities produce social isolation, discrimination and will negatively impact the adult life of these individuals.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The present study showed that, despite Rio Grande do Sul State being historically a low endemic region, diagnoses of new cases in individuals under 15 years old that are multibacillary and present with a high average of physical disability continues to occur. These data are also found in studies in other regions of Brazil, showing that it is necessary to maintain active care and disease control measures, such as: promote training/updates on leprosy to health workers, so that they will think about the diagnosis of leprosy, especially in the early stages of the disease, and continue the annual monitoring of leprosy cases in all Brazilian States 16 , 19 , 20 , 33 . Especially in the studied age group, physical disabilities produce social isolation, discrimination and will negatively impact the adult life of these individuals.…”
Section: Discussionmentioning
confidence: 58%
“…In other studies carried out in Brazil, the average age at diagnosis was similar to that found here 16 . There was variation regarding sex and clinical forms, with some studies showing a predominance of females and multibacillary patients 16 - 18 , and others with a predominance of males and paucibacillary forms, especially the tuberculoid clinical form 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the above-mentioned classifications were also used to classify the clinical forms of childhood leprosy [ 20 ]. It is assumed that the largest number of childhood leprosy cases is in the indeterminate clinical form; however, there was an average proportion (23%) of this form of the disease in a study of the Brazilian childhood population [ 10 ]. A delayed diagnosis may be the reason for this paradox.…”
Section: Classificationmentioning
confidence: 99%
“…In particular, cases still appear in various countries in Southeast Asia, America, Africa, the Eastern Pacific, and the Western Mediterranean [4,9]. Moreover, the high incidence rate in children under 15 years of age is important, indicating that there is early exposure of the population to the bacillus, which is associated with an elevated prevalence in the general population and is a good indicator of high transmission and poor quality of control programs [10][11][12][13][14][15][16]. In the absence of an effective vaccine, early diagnosis and treatment of the disease are important to stop the transmission of M. leprae, reduce the risk of physical disability and deformity, and reduce the physical, psychosocial, and economic burden of the disease [17][18][19].…”
Section: Introductionmentioning
confidence: 99%